Impact of extreme maternal age on neonatal outcomes - Rasamoelison, Rina J.; Rambeloson, Setra H.; Samena, Hanitriniaina S. C.; Robinson, Annick L. (International Journal of Contemporary Pediatrics, 2022)
Background: Pregnancies at extreme ages of reproductive life are considered to be at high risk for mother and neonate. The aim of the study was to determine neonatal risks associated with extreme maternal age. Methods: A retrospective cohort study was conducted at Befelatanana Maternity covering the period from 1 January to 31 December 2018. Data was collected from neonate’s medical files. Results: Of 789 neonates from mothers with extreme age included, 64.7% were from mothers under the age of 18, and 35.3% from mothers aged 40 and over. They were compared to 519 neonates from mothers aged 20-30. Maternal age under 18 was a risk factor for Apgar index below 7 at the 5th minute RR 1.69 (95% CI 1.17, 2.44), preterm birth RR 2.19 (95% CI 1.70, 2.80), low birthweight RR 2.03 (95% CI 1.53, 2.53) and admission to neonatalogy RR 2.64 (95% CI 2.20, 3.16). Also, the neonatal risks of pregnancy after 40 years were fetal death in utero RR 2.97 (95% CI 1.51, 5.85), low birthweight RR 2.47 (95% CI 1.97, 3.10), preterm birth RR 2.85 (95% CI 2.21, 3.68), and admission to Neonatalogy RR 3.06 (95% CI 2.54, 3.68). Conclusions: The extreme age of the mother is therefore a risk of neonatal adverse outcomes. Rigorous prenatal follow-up is needed for these high-risk pregnancies.